The Effect of Olive Oil Concentration in Lip Balm on The Physical Properties and The Product Acceptance Rate - Susilo, Jatmiko; Febriana, Adinda (Universitas Ngudi Waluyo, 2022)
Background: Olive oil contains monounsaturated fatty acids (MUFA) which have potential as antioxidants. Olive oil is used as a moisturizer and softener and protects the skin from the harmful effects of UV rays. The purpose of the study was to analyze the effect of olive oil concentration on the physical properties of lip balm and the level of acceptance of respondents.Methods: Experimental research using olive oil 0; 5; 10 and 15 % as moisturizer and dosage forms were tested for physical properties: organoleptic, homogeneity, pH, and melting point, and the level of acceptance of respondents.Results: F0 indicates the product is unstable during storage and the lowest acceptance rate; F1 (10%) showed stable, but homogeneity, and melting point are unstable, and the third rank acceptance; F2 (10%) showed stable and the first acceptance rank and F3 (15%) shows stable physical properties and the second rank acceptance.Conclusion: Olive oil concentration affects the physical properties (smell, color, texture,pH, and melting point) of lip balm and the level of acceptance. F2 is a formula that has stable physical properties and the highest acceptance rate.Keywords: olive oil, lip balm, physical properties, acceptance rateABSTRAKLatar Belakang: Minyak zaitun mengandung asam lemak tak jenuh tunggal (MUFA) yang berpotensi sebagai antioksidan. Minyak zaitun dimanfaatkan sebagai pelembab dan pelembut dan melindungi kulit dari efek buruk sinar UV. Tujuan penelitian ini untuk menganalisis pengaruh konsentrasi minyak zaitun terhadap sifat fisik lip balm dan tingkat penerimaan produk.Metode: Penelitian eksperimental menggunakan minyak zaitun 0; 5; 10 dan 15 % sebagai bahan pelembab dan produk diuji sifat fisik: organoleptis, homogenitas, pH, dan titik lebur, dan tingkat penerimaan responden.Hasil Penelitian: F0 menunjukkan produk tidak stabil selama penyimpanan dan tingkat penerimaan terendah, F1 (10%) menunjukkan sifat fisik stabil, namun homogenitas, dan titik lebur tidak stabil, dan penerimaan peringkat tiga, F2 (10%) menunjukkan sifat fisik stabil dan penerimaan peringkat pertama dan F3 (15%) menujukkan sifat fisik stabil dengan penerimaan peringkat kedua.Kesimpulan: Konsentrasi minyak zaitun mempengaruhi sifat fisik (tekstur, warna, pH, dan titik leleh) pelembab bibir, dan tingkat penerimaan responden. F2 merupakan formula dengan sifat fisik stabil dan tingkat penerimaan tertinggi.Kata Kunci: minyak zaitun, pelembab bibir, sifat fisik, tingkat penerimaan